2008
DOI: 10.1002/jmor.10595
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the spermatheca and of the accessory glands inOrchesella villosa(Collembola, Hexapoda)

Abstract: The spermatheca and the accessory glands of the collembolan Orchesella villosa are described for the first time. Both organs exhibit ultrastructural differences, according to the time of the intermolt in which the specimens were observed. A thick cuticular layer lines the epithelial cells of the accessory glands. In the reproductive phase, they are involved in secretory activity; a moderately dense secretion found in the apical cell region opens into the gland lumen. Cells with an extracellular cistern are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…This great difference, with respect to Arthropleona, is worthy of discussion. In the Arthropleona Orchesella villosa (and in Pogonognathellus flavescens, personal observations) only one spermatheca is present and it is flanked by two accessory glands (Dallai et al, 2008). The function of these glands in Collembola is not yet known, but considering that they are very close to the genital opening and that females that have picked up spermatophores lay eggs within 1 h Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This great difference, with respect to Arthropleona, is worthy of discussion. In the Arthropleona Orchesella villosa (and in Pogonognathellus flavescens, personal observations) only one spermatheca is present and it is flanked by two accessory glands (Dallai et al, 2008). The function of these glands in Collembola is not yet known, but considering that they are very close to the genital opening and that females that have picked up spermatophores lay eggs within 1 h Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The male deposits spermatophores on the soil and the female picks them up to fertilize her eggs. In a recent paper we described the spermatheca and two accessory glands in the collembolan Arthropleona Orchesella villosa (Dallai et al, 2008). We clarified the nature of the lateral ectodermal pockets [the so called ''accessory organs'' of Tullberg (1872)] close to the female genital opening, establishing that they are true accessory glands.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Females subsequently choose among male ejaculates for internal fertilization, similar to female-biased sperm use in conventional mating systems. But in dissociated systems, fertilization choice takes place outside the female tract, making it easy to observe a male's ejaculate fertilization success [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Females of the genus Orchesella pick up only one spermatophore [12,13] and do not store sperm [13]; hence, postcopulatory cryptic choice is absent. Earlier work on O. cincta has demonstrated that female choice based exclusively on assessment of spermatophores provides the females with indirect benefits [16].…”
Section: Introductionmentioning
confidence: 99%